(untitled) (Revista Española de Derecho Internacional, 2009)
This paper discusses the interpretations given by international tribunals, particularly the one given by the International Court of Justice, to the rule on the delimitation of marine areas between states, focusing on the boundary delimitation methodology applied, in order to identify a potential development or change in the treatment of said issue in the recent years. It also aims to present the new current trends for the achievement of greater legal reliability and predictability in this area. Likewise, the work addresses the major aspects in boundary delimitation methodology in the Case Concerning Territorial and Maritime Dispute between Nicaragua and Honduras in the Carribbean Sea (Nicaragua v. Honduras), and offers some critical comments on this matter.